PEMERTAHANAN DIALEK BANYUMAS TERHADAP DOMINASI DIALEK SOLO-YOGYA - I Dewa Putu Wijana (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2005)
This essay is about the maintenance of Banyumas dialect. This dialect is considered more inferior compared to its standard variant of the Solo-Yogya dialect. Because of its less prestigous status, the speaker of this rural variant, especially those who belong to the younger and educated generation do not speak their own native tongue anymore, but shift to a wider means of communication, the standard variant, Yogya Solo dialect or their national language, Bahasa Indonesia. There are at least two ways which should be carried out to maintain the existence of Banyumas dialect. Firstly the government must create a condition which allows its speakers to use their mother tongue and pass it down to younger generation. Secondly, all Banyumas speakers should posses linguistic pride and awareness that all languages are linguistically the same. Differences in status which exist between languages are a matter of social judgment.